Alat Bantu Tunanetra Menggunakan Sensor Ultrasonik Berbasis Arduino Nano - Syarif Ishak Allkadri (entries, 2023)
Technological advances have a continuous impact on human life needs. Materialistic tendencies, indifference, and empathy will have an impact on people who have special needs (disabilities). Disabilities need the help of other people to carry out their daily activities so that it makes them dependent on other people to live their lives to help them with their activities, the blind use their assistive senses in carrying out their activities. This research aims to produce smart watches that can help blind people to guide the way and detect a safe distance of obstacles around the blind. The design of this smart watch is designed using makeshift materials like watches, the sensor used uses an ultrasonic sensor, the programming code uses Arduino Nano. In making this tool, it is done by calculating the required components. After knowing the specifications of the components, only then can the calculations be made for the Draft Budget (RAB) which will be recommended in making blind aids. And Research and Development is a method used to create the desired product, and is applied as a tool to test the effectiveness of the product. Results Testing this tool was carried out in two stages. The first stage is carried out on a stationary object and the second stage is carried out on a moving object or a walking person. From the results of the two stages, namely the stationary stage and the moving object stage, this tool functions by producing sound at a maximum distance of 50 cm. And at a distance of 100 cm the tool does not even make a sound. Keywords: Disability, Blind watches, Arduino Nano.